Ecological condition of post-industrial towns of Ukraine based on the case study of Drohobych town - Oksana Terletska (Kazimierz Wielki University, 2018)
The current state of most of former powerful industrial cities and towns of Ukraine is characterized by industrial decline; therefore, their ecological condition was expected to improve. Drohobych is a striking example of such a town. The notion "post-industrial" used in the research work, on the one hand, designates the phase after the industrial phase (the one that lasted before the industrial crisis), and on the other hand, it is used to denote the phenomenon of industrial reduction, i.e. significant decrease of industrial potential. The aim and objectives of the research article were dedicated to the study of current ecological state of Drohobych urban environment based on certain research material, as well as detection of the most ecologically threatening season conditions. Based on the elaborated large-scale map of urban landscapes of Drohobych and with the help of the original author's experimental material, there has been represented the current ecological state of natural components (surface and municipal, soils, atmosphere) within the territory of the town of Drohobych. It has been determined that each of the aforementioned components of the urban environment is associated with chemical compounds exceeding maximum allowable concentrations. Moreover, the most threatening values in terms of bacteriological quality are related to the quality of surface and municipal waters. The most hazardous situation occurs during spring period since due to worn-out condition of the pipelines, snowmelt waters leak in municipal water supply network. The same situation can be observed in water from open wells, which is used by the population for drinking. During the research process, there have been analysed disturbing ecological situations, some of which could be characterized as critical. The research works prove the popular idea that ecological condition of Ukrainian post-industrial cities and towns significantly improved after the cessation of many large enterprises to be wrong.